Dysfunction of goal‐directed control in patients with depression and nonsuicidal self‐injury. Issue 6 (19th May 2022) - Chen, Qi; Liu, Meng; Wen, Rongzhen; Xu, Chuanyong; Wei, Zhen; Zhang, Wei; Seger, Carol A.; Peng, Ziwen
Abstract: Background: Non‐suicidal self‐injury (NSSI) is a common problem associated with dangerous outcomes. Dysfunction of goal‐directed behavioral control may contribute to NSSI. To test this, we used a novel experimental paradigm (Pavlovian‐to‐Instrumental Transfer, PIT) to test whether patients with NSSI utilize Pavlovian conditioned stimuli (CSs) during goal‐directed control of ongoing behavior. Methods: Thirty‐five depressed patients with NSSI (D‐NSSI) and thirty‐four healthy controls performed a PIT task. We measured the influence of positive and negative background CSs on instrumental responses for rewards. Results: The results showed that D‐NSSI performed significantly lower PIT than controls, and PIT measures were negatively correlated with NSSI frequency. Furthermore, in a subset of patients exhibiting high levels of compulsivity, PIT positively moderated the relationship between compulsivity and NSSI frequency. Conclusions: These results indicate that D‐NSSI patients have difficulties in using different CSs to control ongoing behavior in a goal‐directed manner, and the dysfunction of goal‐directed control may contribute to NSSI. Abstract : 1. Pavlovian‐to‐Instrumental Transfer (PIT) as a measure of goal‐directed behavior. 2. Patients with depression and nonsuicidal self‐injury (D‐NSSI) showed significantly lower PIT than controls. 3. PIT measures were negatively correlated with NSSI frequency.